Impacts of studying in a regional medical campus on practice location (Canadian Medical Education Journal, 2018)
Background: New Brunswick, a bilingual Canadian province without a medical school, negotiated an agreement in 1967 in which places were reserved for francophone medical students in the province of Quebec. In 2006, the Centre de Formation Médicale du Nouveau-Brunswick (CFMNB), a regional medical campus (RMC) of Université de Sherbrooke for its provincial francophone medical students, was established to increase the likelihood of graduates setting up practice in the region. Practice locations of the initial 5 cohorts of CFMNB were analysed to compare data with francophone students trained in Quebec.Methods: Practice locations were determined through Scott’s Medical Database and provincial public registries.  Chi-square and relative risk probability were used to examine the relationship between training location and practice location.Results: Doctors trained at CFMNB were 1.4 times more likely to be practicing in Atlantic Canada compared to those trained at Université de Sherbrooke (main campus) before 2006. Those trained at CFMNB were 1.3 times more likely to go on to practice in the region compared to those trained at Université Laval or Université de Montréal. Conclusion: This study supports the hypothesis that individuals completing a medical program in a Francophone RMC in New Brunswick increases the likelihood of them later practicing in the province or in the wider Atlantic Canada region._______Contexte: Le Nouveau-Brunswick, une province canadienne bilingue ne possédant pas de Faculté de médecine, a négocié en 1967 une entente avec le Québec afin de réserver des places pour ses étudiants francophones souhaitant étudier la médecine.  En 2006, le Centre de formation médicale du Nouveau-Brunswick (CFMNB), un campus médical régional (CMR) de l’Université de Sherbrooke, a été créé afin de permettre aux Néo-Brunswickois d’étudier la médecine en français dans leur province.  L’un des objectifs principaux du CFMNB était d’augmenter les probabilités que les diplômés en médecine s’établissent dans la région.  Les lieux de pratique des médecins issus des 5 premières cohortes du CFMNB ont été analysés afin de les comparer avec ceux des médecins francophones d’origine néo-brunswickoise formés au Québec.Méthodes: Les lieux de pratique ont été déterminés via le répertoire des médecins Scott’s et les registres publics provinciaux.  Des tests de Chi carré et des analyses de risque ont été conduits afin d’étudier la relation entre le lieu de formation et le lieu de pratique.Résultats: Les médecins formés au CFMNB étaient 1.4 fois plus enclins à travailler au Canada atlantique comparativement à ceux formés au campus principal de l’Université de Sherbrooke avant 2006.  Les médecins formés au CFMNB étaient également 1.3 fois plus enclins à travailler dans la région que ceux formés à l’Université Laval ou à l’Université de Montréal.Conclusion: Cette étude supporte l’hypothèse selon laquelle le fait de compléter un programme de médecine francophone dans un CMR francophone au Nouveau-Brunswick augmente les chances de pratiquer au Nouveau-Brunswick ou dans la grande région du Canada atlantique.